2007
DOI: 10.1128/iai.01358-06
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Staphylococcal Enterotoxin C1 Exposure Induces Soluble Factor-Mediated Immunosuppression by Bovine CD4+and CD8+T Cells

Abstract: Regulatory T cells (T regs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 47 publications
(43 reference statements)
4
37
0
Order By: Relevance
“…Total RNA was extracted as described previously (Rebeil et al, 2006). Reverse transcription with hexanucleotides (Roche), real-time PCR using the SYBR green I dye master mix and an ABI 7000 thermocycler (Perkin-Elmer Applied Biosystems), and data analysis were as described previously (Seo et al, 2007). Relative quantities of mRNA were normalized to the amount of proS mRNA in the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted as described previously (Rebeil et al, 2006). Reverse transcription with hexanucleotides (Roche), real-time PCR using the SYBR green I dye master mix and an ABI 7000 thermocycler (Perkin-Elmer Applied Biosystems), and data analysis were as described previously (Seo et al, 2007). Relative quantities of mRNA were normalized to the amount of proS mRNA in the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Foxp3 currently represents the most specific marker used to distinguish regulatory cells (Foxp3 + CD25 + CD4 + ) from activated effector cells (Foxp3 − CD25 + CD4 + ) within the CD25 + CD4 + cell subpopulation. Interestingly, Hoek et al [7] demonstrated that bovine WC1.1 + and WC1.2 + γδ cells rather than Foxp3 + CD25 high CD4 + cells act as immune regulatory cells ex vivo, however, the results of a study conducted by Seo et al [11] showed that there are certain cells with regulatory properties among bovine CD4 + and CD8 + cells.Although CD4 + regulatory T cells are the best-studied and characterized regulatory lymphocytes, in recent years, substantial progress has been made in the phenotypic and functional characterization of CD8 + T regulatory cells. Foxp3 + CD25 + CD8 + cells are one of the better-described regulatory subsets in the CD8 + T cell population.…”
mentioning
confidence: 55%
“…Whether these cells were bona fide Tregs or activated Tcons, which in some assay systems are capable of mediating non-specific suppression [354,355], remains unclear. A number of subsequent studies presented indirect evidence for populations of CD4 + , CD8 + and γδ T cells with regulatory activity [355][356][357][358][359][360][361], but T cells expressing FOXP3 were first documented in 2009: thus, Seo and colleagues developed novel mAbs against bovine FOXP3, demonstrating that its expression was limited to CD4 + CD25 + T cells [362], while Gerner and colleagues documented cross-reactivity of the antimouse/rat Foxp3 mAb FJK-16s, showing that the majority of FOXP3 + T cells were CD4 + but that minor populations of CD8β + and γδ + FOXP3 + lymphocytes could also be identified [363]. However, the regulatory properties of the CD4 + CD25 high FOXP3 + population were called into question by work performed by Hoek and colleagues, who suggested that these cells were neither anergic nor suppressive; rather, WC1.1 + and WC1.2 + γδ T cells, and CD14 + monocytes, showed regulatory properties in their experiments, supported by the observation that these cells transcribed IL-10 [364].…”
Section: Regulatory T Cells In Other Domestic Animal Species -An Expamentioning
confidence: 96%